E-commerce and prices: Theory and evidence - Richard Friberg; Mattias Ganslandt; Mikael Sandström (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
This paper examines the relation between prices in conventional stores and on the Internet. Main results from the theoretical analysis are i) we expect a discrete fall in prices in conventional stores as the share of the population with access to Internet reaches a critical level, ii) the relation between prices depends on convenience costs of shopping in regular stores as well as on transport and navigation costs for goods bought over Internet, iii) retailers who only sell through Internet have lower on-line prices than retailers who also sell through conventional stores. The empirical section employs a rich data set covering the Swedish markets for books and CDs. Prices of these goods are on average 15 percent lower on Internet, but if a single item is bought transport costs will make it as expensive to buy over Internet as in a regular store (if a basket of goods is bought it is some 10 percent cheaper on Internet since transport costs are fixed). There is firm support for that retailers who only sell over Internet have lower on-line prices.
Keywords: D12; D43; L11; L81; 330; retail pricing; consumer behavior; e-commerce; price discrimination; Internet; E-Business; Einzelhandel; Preisniveau; Vergleich; Theorie